Development of ispring-assisted interactive learning media to support students self-regulated learning on flat-sided geometric solids - Nainggolan, Susy Irawaty; Heleni, Susda; Suanto, Elfis (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This research was motivated by the importance of fostering student independence in learning, particularly through the development of self-regulated learning, which does not emerge without external support. The aim of this study is to develop interactive learning media assisted by iSpring that meet the criteria of validity and practicality, in order to support students self-regulated learning and help eighth-grade junior high school/madrasah students understand the topic of flat-sided geometric solids. The development process follows the ADDIE model. The test subjects consisted of eighth-grade students at SMPN 20 Pekanbaru. Data were collected through interviews and questionnaires, using instruments such as expert validation sheets, student response questionnaires, and a self-regulated learning questionnaire. Validation results indicated that the media was classified as very valid with an average score of 3.76. In the small group trial, student responses yielded an average score of 0.92 (very practical), while the self-regulated learning score averaged 77.51% (good). In the large group trial, student responses had an average score of 0.81 (practical), and the self-regulated learning score was 79.61% (good). These results indicate that the developed learning media meets the criteria of being both valid and practical.